Shielding application with the reduction of undesirable reception channels of subscriber satellite navigators - A. S. Abukraa; M. A. Vilkotsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
General questions of the effect of screens on the parameters of antennas of subscriber navigators are considered. The effect on their parameters of impedance screens, as well as resonance type screens, is considered. The obtained results are used as initial data for the analysis of the parameters of the systems formed by screens and weakly directional user navigation receivers. The characteristics of receiving antennas of strip and vibrator structures with screens of absorbing and impedance type, as well as their modifications in the form of compact in the folded state of structures, are studied. The possibilities of using conformal screen designs are discussed. An attempt to evaluate their optimality is done.